Draft Annual Plan 2003-2004 Volume I Government of Assam - Planning Commission (Planning Commission, 2003)
Assam, the gateway to the beautiful North Eastern Region of India, today is a State with a mission. The ‘Mission’ is to accomplish accelerated development Assam by overcoming both natural and man made barriers to growth. Assam has been eternally blessed with a bountiful nature. The blue mountains with a wide array of fauna and flora; the mighty Brahmaputra and its tributaries providing abundant water resources; the dense forests covering wide range of medicinal plants, the oil and natural gas; the fertile valleys and hill slopes nourishing tea gardens, horticultural crops and vital food grains cumulatively provide immense possibilities for economic development.
Planning & Development Department Government of Assam